A Quinol Anion as Catalytic Intermediate Coupling Proton Translocation With Electron Transfer in E. coli Respiratory Complex I - Nuber, Franziska; Mérono, Luca; Oppermann, Sabrina; Schimpf, Johannes; Wohlwend, Daniel; Friedrich, Thorsten (Frontiers in Chemistry, 2021)
Energy-converting NADH:ubiquinone oxidoreductase, respiratory complex I, plays a major role in cellular energy metabolism. It couples NADH oxidation and quinone reduction with the translocation of protons across the membrane, thus contributing to the protonmotive force. Complex I has an overall L-shaped structure with a peripheral arm catalyzing electron transfer and a membrane arm engaged in proton translocation. Although both reactions are arranged spatially separated, they are tightly coupled by a mechanism that is not fully understood. Using redox-difference UV-vis spectroscopy, an unknown redox component was identified in Escherichia coli complex I as reported earlier. A comparison of its spectrum with those obtained for different quinone species indicates features of a quinol anion. The re-oxidation kinetics of the quinol anion intermediate is significantly slower in the D213GH variant that was previously shown to operate with disturbed quinone chemistry. Addition of the quinone-site inhibitor piericidin A led to strongly decreased absorption peaks in the difference spectrum. A hypothesis for a mechanism of proton-coupled electron transfer with the quinol anion as catalytically important intermediate in complex I is discussed.